An Article Review on “Reading Comprehension Strategy Instruction in a First-Year Course: An Instructor’s Self-Study” - Budiarti, Vira; Syafitri, Yona Dwi Tirta; Derin, Tatum (Elsya : Journal of English Language Studies, 2019)
This study aims to provide insight for others who wish to do a self-study, discussing emerging themes related to student learning and strategy instruction at the post-secondary level. This study reviews a research article written by Parr & Woloshyn (2013), entitled “Reading Comprehension Strategies Instruction in a First-Year Course: An Instructor's Self-Study.” Results of the review include observations on how the related article doesn't adequately deliver objectives but is excellent at analyzing the previous literature, and the design of the research will make readers understand generally. The contents of this article are valid with all references used accurately. It concisely discussed reading comprehension and strategy instruction. Also, it used a robust theoretical framework that provides an opportunity to reflect the challenges and limitations associated with the application of explicit strategy instruction. Ultimately, this present study looks at independent learning instruction as a strategy in delivering a repertoire of evidence-based understanding strategies designed to introduce students to the conventions of reading and writing academics. This study especially entices educators, because this study can be a benchmark for lecturers to provide reading comprehension strategy in a first years course, especially reading skill.